Prakseologiczne podstawy czynności kierowania szkolnym procesem poznawania dzieła literackiego w szkole = Praxiologic Essentials for Guiding the School Process of Perception of a Piece of Literary Work in School - Krauze, Urszula (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The authoress of this paper explicates the principle of the leading part of teachers in the didactic and educational process, expressed by modern didactics, and assumes, that education in reality is the organization of circumstances and situations, which are conducive best to the process of maturation, self-education and self-upbringing and of guiding these processes.These thesises were motivated and elaborated by citation of praxiology, by theory of organization and guiding as well as by the theory of systematic teaching and learning literature.
Keywords: prakseologia; dzieło literackie; język polski - nauczanie